(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the issue of stress management and psychological resilience in football players. In modern sports environments, high levels of stress, pressure, and competition can negatively impact the effectiveness of footballers’ performance. Therefore, it is crucial to thoroughly study stress management methods and techniques for developing psychological resilience. The article analyzes ways to reduce stress through the use of psychological training, meditation, and concentration exercises. The significance of motivational strategies, self-control, and team support in enhancing psychological resilience is also investigated. The research findings are aimed at developing practical recommendations for preserving the mental health of footballers and improving their performance in competitions. This article is intended for professional footballers, coaches, and sports psychologists.